2010
DOI: 10.1111/j.1464-410x.2009.08795.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bladder tumour growth by histone deacetylase inhibitor

Abstract: reaction and immunohistochemical methods. Female C3H/He mice were given VPA (0, 250, 500 and 750 mg/kg body weight, intraperitoneal, every day) from the start or 4 weeks after 0.05% N -butyl-N-(4-hydroxybutyl)-nitrosamine (BBN) treatment, and were humanely killed and sampled at 8 and 12 weeks. RESULTSA significantly higher level of HDAC1 mRNA was expressed in human urinary bladder cancer specimens. The immunohistochemical study showed that HDAC1 was expressed in the cytoplasm and nucleus in the specimens. BBN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 20 publications
1
30
0
2
Order By: Relevance
“…Valproic acid not only suppressed some tumor growth and metastasis, but also induced tumor differentiation in vitro and in vivo (Blaheta and Cinatl 2002). Valproic acid inhibited the in vitro and in vivo cancer cell growth of melanoma (Landreville et al 2012), urinary bladder cancer (Byun et al 2009;Ozawa et al 2010), breast cancer (Munster et al 2009), and prostate cancer (Chou et al 2011). Recently, the combination of valproic acid with other anticancer agents has been considered as a useful and necessary strategy to inhibit tumor growth and progression (Byun et al 2009;Munster et al 2009;Ozawa et al 2010;Chou et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Valproic acid not only suppressed some tumor growth and metastasis, but also induced tumor differentiation in vitro and in vivo (Blaheta and Cinatl 2002). Valproic acid inhibited the in vitro and in vivo cancer cell growth of melanoma (Landreville et al 2012), urinary bladder cancer (Byun et al 2009;Ozawa et al 2010), breast cancer (Munster et al 2009), and prostate cancer (Chou et al 2011). Recently, the combination of valproic acid with other anticancer agents has been considered as a useful and necessary strategy to inhibit tumor growth and progression (Byun et al 2009;Munster et al 2009;Ozawa et al 2010;Chou et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…High expression levels of class I HDACs correlated with tumour dedifferentiation and higher proliferative fractions (measured by Ki-67) in urothelial carcinoma, which is in line with in vitro studies showing that high HDAC activity leads to tumour dedifferentiation and enhanced tumour cell proliferation [28][29][30]. Despite the growth inhibitory effects of HDAC-i demonstrated in various cell lines including bladder cancer cells, a broad expression analysis of this attractive target has not been conducted yet [12][13][14][15][16]31,32].…”
Section: Discussionmentioning
confidence: 62%
“…In contrast to these findings, a more recent study of Xu and colleagues reported no difference of expression in the expression levels of HDAC-2 between normal urothelial and bladder cancer tissue as assessed by immunohistochemistry [13]. Few studies have found an effect for HDAC-inhibitors (HDAC-i) in urothelial cancer cell lines [12,[14][15][16][17], however, a broad expression analysis of HDACs in urothelial carcinomas has not been conducted so far. In addition, there is no study available on the prognostic relevance of class I HDACs in bladder cancer.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent studies showed that aberrant expression of HDAC1 was found in various types of cancer cells, which suggested that the HDAC1 expression was associated with tumor progress and differentiation. For example, Ozawa A found that the expression level of HDAC1 mRNA in human urinary bladder cancer specimens was significantly higher than that of normal controls [3]. Also, increased mRNA expressions of HDCA1, HDAC2 and HDAC3 were detected in ovarian cancer tissues, compared to normal tissue samples [4].…”
Section: Introductionmentioning
confidence: 99%